2015
DOI: 10.1007/s12022-015-9386-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathology of Follicular Cell Nodules

Abstract: This article corresponds to a lecture delivered during the Endocrine Pathology Society symposium held in Boston on 21 March 2015 (104th USCAP meeting, March 21-27). It focuses on the importance of cytopathology in endocrine thyroid pathology and the limits and pitfalls of diagnosis in follicular cell lesions. Lights and shadows are present in each diagnostic technique: Fine needle aspiration has imposed itself as a gold standard in thyroid nodules thanks to its easiness of execution and high cost-effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…[1][2][3][4][5] The remaining nodules (20% to 25%) represent the "gray zone" of follicular/indeterminate lesions that belong to indeterminate categories according to TBSRTC. [6][7][8][9][10][11][12][13][14][15][16][17][18] Difficulties and limitations in morphologically discriminating whether these nodules are benign or malignant entities has led to unnecessary surgical resections (lobectomy or total thyroidectomy) and has raised health care costs accordingly. 4,5 Patients with indeterminate nodules that undergo surgical resection often turn out to have benign thyroid nodules or only indolent neoplasms, including NIFTP.…”
Section: Molecular Profiling Of Thyroid Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] The remaining nodules (20% to 25%) represent the "gray zone" of follicular/indeterminate lesions that belong to indeterminate categories according to TBSRTC. [6][7][8][9][10][11][12][13][14][15][16][17][18] Difficulties and limitations in morphologically discriminating whether these nodules are benign or malignant entities has led to unnecessary surgical resections (lobectomy or total thyroidectomy) and has raised health care costs accordingly. 4,5 Patients with indeterminate nodules that undergo surgical resection often turn out to have benign thyroid nodules or only indolent neoplasms, including NIFTP.…”
Section: Molecular Profiling Of Thyroid Lesionsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Several authors have demonstrated that the likelihood of an SFN/FN nodule being neoplastic is 65% to 85%, whereas that for the ROM is significantly lower (25% to 40%). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Most of these malignancies are interpreted histologically as PTC ( Fig. 1), comprising mostly FVPC (Table 3).…”
Section: Molecular Test Options and Molecular Approach To Indeterminamentioning
confidence: 99%
“…The Endocrine Pathology Society proposed a formal reclassification, treating NI-FVPTC as a benign neoplasm [34]. The researchers analyzed 5 studies from 5 institutions, [9,35,36]. Moreover, they concluded that after reclassification due to the decrease in RM there should be an indication for lobectomy instead of a thyroidectomy in many cases [9].…”
Section: Discussionmentioning
confidence: 99%
“…Fine needle aspiration is invariably the best method of preoperative diagnostics and rational triage of patients to surgical treatment or observation [5,14]. In the case of DC VI ("malignant" diagnosis), the recommended treatment is thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Special attention has recently been given to the encapsulated non-invasive follicular variant of papillary thyroid carcinoma: NI-FVPTC due to its indolent course. It is proposed to treat this tumor as an adenoma [14,17,37,38,39]. It is often difficult, though, to assess the capsular invasion if the patient had multiple biopsies and the capsule has features that cause difficulties in distinguishing between capsular damage and invasion.…”
Section: Discussionmentioning
confidence: 99%